Adaptation of the Performance Enhancement Attitudes Scale to Individuals Doing Exercise Regularly in Turkey: A Cross-Sectional Study - Bashan, Ibrahim; Toros, Turhan; Yasa Ozturk, Gulsah; Uysal, Yucel; Coskun Ozyol, Funda; Guzel, Sinan (Progress in Nutrition, 2022)
Study Objectives: The aim of this study was to adapt the internationally accepted Performance Enhancement Attitude Scale to the Turkish culture and determine the reliability and validity of the adapted version. Methods: A total of 207 Turkish individuals, 110 males (mean age=39.33±2.45 years) and 97 females (mean age=38.91±1.51 years), aged 18 and over, who regularly engaged in exercise, participated in the study. In the analysis of the data, the exploratory factor analysis was used to determine the underlying structure of the scale items, and the confirmatory factor analysis was performed to test the compatibility between the model and the data. In addition, the Cronbach alpha reliability analysis was undertaken for reliability, and the Pearson product-moment correlation and test-retest values were obtained to examine for the item correlation analysis. Results: The cross-sectional multi-sample Performance Enhancement Attitude Scale consisted of 17 independent items under a single sub-dimension as in the original version. In our study, the internal consistency coefficient of the Turkish version was calculated as 0.88, the factor loads varied between 0.40 and 0.67, and the test-retest correlation was 0.79. Conclusions: These findings showed that the Turkish adaptation of the Performance Enhancement Attitude Scale can be reliably used for research purposes. It may be thought that is important to bring an internationally accepted instrument to the Turkish literature to be used in future research in order to investigate the performance-enhancing attitudes of exercise.